2014
DOI: 10.14260/jemds/2014/1820
|View full text |Cite
|
Sign up to set email alerts
|

Co-Relation Between First Trimester Uric Acid Concentration and Development of Gestational Diabetes Mellitus

Abstract: Gestational diabetes mellitus (GDM) is defined by the World Health Organization (WHO) as a carbohydrate intolerance resulting in hyperglycemia of varying severity with onset or first recognition during pregnancy 1 (WHO, 1999). The present study was done to find out the correlation between 1 st trimester uric acid concentration and the development of GDM. GDM was diagnosed based on the OGCT and GTT test. Study was done in a total of 1002 patients. Uric acid concentration of >3.6mg/dl was considered abnormal (AJ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…In the present study 58.9% are primigravida and 41.1% are multigravida, from which 22% of primigravida and 24% of multigravidas developed GDM; similarly, Rajakumar et al study included 63.5% Primigravida and 36.4% multigravida and there was no difference in SUA at 1 st trimester in relation to parity. 21 In contrast Nagalakshmi et al has reported a higher risk of GDM among multigravida. In the present study 36% of the women had risk factors for development of GDM like elderly primigravida, PCOD, obesity, hypothyroidism, and diabetes mellitus among 1 st degree relatives and 31% of them developed GDM.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In the present study 58.9% are primigravida and 41.1% are multigravida, from which 22% of primigravida and 24% of multigravidas developed GDM; similarly, Rajakumar et al study included 63.5% Primigravida and 36.4% multigravida and there was no difference in SUA at 1 st trimester in relation to parity. 21 In contrast Nagalakshmi et al has reported a higher risk of GDM among multigravida. In the present study 36% of the women had risk factors for development of GDM like elderly primigravida, PCOD, obesity, hypothyroidism, and diabetes mellitus among 1 st degree relatives and 31% of them developed GDM.…”
Section: Discussionmentioning
confidence: 92%
“…Similar finding of elevated 1 st trimester SUA levels with different cut-off values by multiple authors are compared in Table 3. 9,11,13,[21][22][23][24][25][26][27][28] Mean SUA in No GDM group in the present study is 3.1±0.7mg/dl and in GDM group it is 3.5±0.9mg/dl and when this cut-off point (≥3.5mg/dl) is employed, it is also found to be statistically significant in predicting at risk women for development of GDM with 'p' values of 0.023 when equal variances assumed and 0.038 when equal variances are not assumed. From this and study of other researchers it appears that, it may not be helpful to employ a cut-off value for SUA of <3.2mg/dl in 1 st trimester to determine women at risk for development of GDM.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, 19 studies were excluded after the full-text screening. Finally, 23 studies were eligible for inclusion in the present study [18][19][20][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] . Table 1 summarizes the characteristics of the included studies.…”
Section: Characteristics Of Included Studies and Quality Assessmentmentioning
confidence: 99%
“…The maternal blood uric acid concentration during pregnancy was measured in 21 of 23 studies at or before the 20th week of gestation [18][19][20]25,[27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] , and the remaining studies measured it after the 20th week of gestation 26,44 . The maternal blood uric acid concentration during pregnancy was measured using calorimetric assays 18,20,25,27,28,[30][31][32][33][36][37][38][39]41 or a spectrometric method 29 , whereas eight out of 23 included studies did not provide data regarding the method of maternal blood uric acid measurement 19,26,34,35,40,[42][43][44] . Among the 23 included studies, five studies collected blood samples after 8-12 h of fasting for the measurement of maternal uric acid…”
Section: Characteristics Of Included Studies and Quality Assessmentmentioning
confidence: 99%
See 1 more Smart Citation